Laboratory of the Present - Angela Palumbo (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The Architecture Biennale is entrusted with the mission of being a sensor of the future through a collection of possible actions in the present on a global scale. The 18th Laboratory of the Future Exhibition curated by Lesley Lokko was born with the intention of being a laboratory place, as the title itself declares, but in reality it denies, by deciding not to deal with, a decisive issue for the planning of the future: the city. Lee Kuan Yew's quote in Singapore Songlines "Singapore is a very small place, in a very large, varied and changing world, and unless it is nimble and quick to adapt, it will perish and the people know it", underlines the strength of urban acceleration. The life system of African cities, crazy and incomprehensible, but at the same time contemporary, makes them the ideal case to ask the question: what will the cities of the future be like?